DNA methylation of Th2 lineage determination genes at birth is associated with allergic outcomes in childhood. Issue 12 (31st August 2017) - Barton, S. J.; Ngo, S.; Costello, P.; Garratt, E.; El‐Heis, S.; Antoun, E.; Clarke‐Harris, R.; Murray, R.; Bhatt, T.; Burdge, G.; Cooper, C.; Inskip, H.; et al.
Summary: Background: There is now increasing evidence that asthma and atopy originate in part in utero, with disease risk being associated with the altered epigenetic regulation of genes. Objective and Methods: To determine the relationship between variations in DNA methylation at birth and the development of allergic disease, we examined the methylation status of CpG loci within the promoter regions of Th1/2 lineage commitment genes (GATA3, IL‐4, IL‐4R, STAT4 and TBET) in umbilical cord DNA at birth in a cohort of infants from the Southampton Women's Survey (n = 696) who were later assessed for asthma, atopic eczema and atopy. Results: We found that higher methylation of GATA3 CpGs −2211/−2209 at birth was associated with a reduced risk of asthma at ages 3 (median ratio [median methylation in asthma group/median methylation in non‐asthma group] = 0.74, P = .006) and 6‐7 (median ratio 0.90, P = .048) years. Furthermore, we demonstrated that the GATA3 CpG loci associated with later risk of asthma lie within a NF‐κB binding site and that methylation here blocks transcription factor binding to the GATA3 promoter in the human Jurkat T‐cell line. Associations between umbilical cord methylation of CpG loci within IL‐4R with atopic eczema at 12 months (median ratio 1.02, P = .028), and TBET with atopy (median ratio 0.98, P = .017) at 6‐7 years of age were also observed. Conclusions and Clinical Relevance: Our findings provide further evidence of a developmental contribution to the risk of later allergic disorders and suggest that involvement of epigenetic mechanisms in childhood asthma is already demonstrable at birth.